Membangun Komunitas Katolik Yang Kuat Di Era Digital - Maria Caritas Trisian Wae Moda; Intansakti Pius X (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
The digital age presents both opportunities and challenges for Catholic communities. On the one hand, technology opens up a vast and easily accessible gateway to religious education, and facilitates communication and participation in various community activities. On the other hand, technology can also bring negative impacts such as reduced face-to-face interaction, superficial communication, and the spread of misinformation. Building strong Catholic communities in the digital age requires effort and commitment from all parties. Community leaders need to provide proper guidance and direction, as well as utilize technology creatively to reach out to their congregation. Catholics need to actively participate in various community activities, support each other, and develop concern for relevant social and religious issues. Social media can be a powerful tool for building strong Catholic communities in the digital age. Social media can be used to share information and discussions about faith, build global networks to share experiences and resources, develop digital skills to utilize technology in various aspects of life, serve others more effectively, and strengthen the role of individuals in the community. By working together and supporting each other, each individual can play an important role in strengthening the Catholic community. Let us make our communities places of faith, love, and hope that inspire and bless all who are involved.